STRATEGI EDORA SPORTSWEAR DALAM MENINGKATKAN BRAND AWARENESS MELALUI TIKTOK - Jeanie Annissa; Kirana Putri Wardani (Jurnal Komunikasi, 2024)
This study aims to determine the strategy of the Edora Sportswear in increasing brand awareness through Tik Tok. The formulation of the problem of this research is how the strategy carried out by Edora Sportswear Brand Through Tik Tok in Increasing Brand Awareness. The theory of this research uses the concept of Three Ways Strategy from Thomas L. Harris namely Pull Strategy, Push Strategy, and Pass Strategy. The paradigm used is post positivism and a qualitative approach with a descriptive research type. Data collection techniques useing primary and secondary data. The results of this study indicate that the Edora Sportswear wants to maintain the existence of the Muslimah Swimwear brand by using the Three Ways Strategy. Edora Sportsware carries out a pull strategy to attract audience attention, this can be seen by disseminating information about brands through product knowledge and product advertising. The pull strategy is used by Edora Sportswear by using the Tik Tok social media with all the features available. The pass strategy is the final strategy of the Three Ways Strategy used by Edora Sportswear by disseminating educational content, collaborating with waterparks and as a means of consulting